A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities. Issue 2 (17th January 2023) - Wang, Yun; Shi, Dao-Qun; Jiang, Na; Rao, Kai-Rui; Zhang, Shi-Xian; Liu, Dan; Li, Rong-Tao; Li, Hong-Mei
Abstract: A new acylated iridoid, valejatadoid H (1 ), along with fourteen known compounds, were obtained from the n -BuOH extract of the roots and rhizomes of Valeriana jatamansi, and their structures were elucidated by various spectroscopic methods. Among them, compounds 8, 11 and 13 exhibited potent inhibition on NO production, with IC50 values of 4.21, 6.08 and 20.36 μM, respectively. In addition, compounds 14 and 15 showed anti-influenza virus activities, among which compound 14 exhibited significant effect with an IC50 value of 0.99 μM. Graphical Abstract: UF0001